2012
DOI: 10.1037/a0029422
|View full text |Cite
|
Sign up to set email alerts
|

Binds and bounds of communion: Effects of interpersonal values on assumed similarity of self and others.

Abstract: Assumed similarity refers to ascribing similar attributes to the self and others. Because self-other similarity facilitates communion, people who value communion should be prone to assume self-other similarity; but because self-other similarity also evokes obligation, they may be prone to assume similarity only with others with whom they are or would feel comfortable being interconnected. We tested these hypotheses in 5 studies (total N = 1,709). In Study 1, students indicated their political preferences and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
27
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 91 publications
5
27
0
1
Order By: Relevance
“…In the current study, Cronbach’s α for each octant ranged from .73 (PA) to .85 (LM) with a mean α of .80. Research shows the CSIV to have a robust circumplex structure and supports its construct validity (Acton & Revelle, 2002; Locke, 2003; Locke & Christensen, 2007; Locke, Craig, Baik, & Gohil, 2012; Thomas, Kirchmann, Suess, BrĂ€utigam, & Strauss, 2012).…”
Section: Methodsmentioning
confidence: 76%
“…In the current study, Cronbach’s α for each octant ranged from .73 (PA) to .85 (LM) with a mean α of .80. Research shows the CSIV to have a robust circumplex structure and supports its construct validity (Acton & Revelle, 2002; Locke, 2003; Locke & Christensen, 2007; Locke, Craig, Baik, & Gohil, 2012; Thomas, Kirchmann, Suess, BrĂ€utigam, & Strauss, 2012).…”
Section: Methodsmentioning
confidence: 76%
“…From the Optimal Distinctiveness Theory (Brewer, 1991), we know that belongingness needs are fulfilled through self-stereotyping. Work by Locke, Craig, Baik, and Gohil (2012) showed that high belongingness needs result in strong projection of personal preferences onto others. Moreover, in recent unpublished data, we found that the need to belong was positively related to both self-anchoring and self-stereotyping (Van Veelen, Hansen, & Otten, 2015).…”
Section: Implications and Future Perspectivesmentioning
confidence: 99%
“…Social comparisons are not dispassionate assessments; they are social acts shaped by social motives. For example, studies have found that people with stronger communal motives are particularly likely to believe that close others and ingroup members are similar to the self (Locke, Craig, Baik, & Gohil, ), feel happy and connected after noticing similarities between the self and others (Locke, ), judge upward and downward comparisons (that locate oneself below or above others) as harmful (Locke, ), and feel discomfort with being the target of upward comparisons (Zell & Exline, ).…”
Section: Interplay Between Agentic and Communal Motivesmentioning
confidence: 99%